Decompiling Java using staged encapsulation - Miecznikowski, J.; Hendren, L. (Proceedings Eighth Working Conference on Reverse Engineering, 2001)
The paper presents an approach to program structuring for use in decompiling Java bytecode to Java source. The structuring approach uses three intermediate representations: (1) a list of typed, aggregated statements with an associated exception table, (2) a control flow graph, and (3) a structure encapsulation tree. The approach works in six distinct stages, with each stage focusing on a specific family of Java constructs, and each stage contributing more detail to the structure encapsulation tree. After completion of all stages the structure encapsulation tree contains enough information to allow a simple extraction of a structured Java program. The approach targets general Java bytecode including bytecode that may be the result of front-ends for languages other than Java, and also bytecode that has been produced by a bytecode optimizer. Thus, the techniques have been designed to work for bytecode that may not exhibit the typical structured patterns of bytecode produced by a standard Java compiler. The structuring techniques have been implemented as part of the Dava decompiler which has been built using the Soot framework.